![f(x)\text{ = }(1)/(2)x(x\text{ }+2)(x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/6t3jyb14mj4y71zl2nb0fmawl5w94gfwxm.png)
Step-by-step explanation:
To detrmine the formula of the polynomial, we check for the roots on the graph:
when y = 0, x = -2
when y = 0, x = 4
We have two roots.
x = -2
x + 2 = 0
x = 4
x - 4 = 0
3rd factor is x = 0
Hence, we have two factors: x(x + 2) and (x - 4)
The polynomial function using the factors:
![f(x)\text{ = ax(x + 2)(x - 4)}](https://img.qammunity.org/2023/formulas/mathematics/college/ejn5b9c6wpltkewi01tf49plbyoflrybcz.png)
Next, we find the value of a:
To get a , we pick a point on the graph. let the point be (0, -4)
substitute the point in the function above:
![\begin{gathered} f(x)\text{ = y = -4, x = 0} \\ -4\text{ = a(0 + 2) (0 - 4)} \\ -4\text{ = a(2)(-4)} \\ -4\text{ = -8a} \\ a\text{ = -4/-8} \\ a\text{ = 1/2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fm80jnchfq0p78m6plwj6v6jchynixe741.png)
The formula of the polynomial becomes:
![f(x)\text{ = }(1)/(2)x(x\text{ }+2)(x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/6t3jyb14mj4y71zl2nb0fmawl5w94gfwxm.png)